2004
DOI: 10.1080/1351847032000168696
|View full text |Cite
|
Sign up to set email alerts
|

Company investment announcements and the market value of the firm

Abstract: This paper examines the stock market reaction to 402 company investment announcements made by UK companies during the 1991-1996 period. The marketadjusted abnormal returns are generally positive but small. Investment announcements are classified according to functional categories, and we find the level of abnormal returns to vary according to the type of capital investment being announced. In particular, we find the market to react more favourably to investments which 'create' future investment opportunities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Similarly, positive valuation implications have been found in studies of capital expenditure project announcements. Woolridge and Snow (1990) find that strategic investment projects earn positive abnormal returns irrespective of the expected investment horizon, while Jones, Danbolt and Hirst (2004) document that announcements of projects that create growth options are associated with significantly greater market-adjusted returns than announcements of projects that exercise growth options. In their study of the intra-industry effects of US corporate capital expenditure announcements, Chen et al (2007) report a positive impact on announcers' event-period abnormal returns and a net negative effect on competitors' market values, which they consider to be consistent with the competitive advantages suggested by Porter (1979).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Similarly, positive valuation implications have been found in studies of capital expenditure project announcements. Woolridge and Snow (1990) find that strategic investment projects earn positive abnormal returns irrespective of the expected investment horizon, while Jones, Danbolt and Hirst (2004) document that announcements of projects that create growth options are associated with significantly greater market-adjusted returns than announcements of projects that exercise growth options. In their study of the intra-industry effects of US corporate capital expenditure announcements, Chen et al (2007) report a positive impact on announcers' event-period abnormal returns and a net negative effect on competitors' market values, which they consider to be consistent with the competitive advantages suggested by Porter (1979).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The exception was the total return series for Spain general index (IBEX) obtained directly from Bolsa de Madrid. 18 Kothari and Warner (2006) show that the tests are not highly sensitive to the benchmark model of abnormal returns. Market-adjusted returns are not included here for all tests.…”
Section: Abnormal Returnsmentioning
confidence: 99%
“…found that there are differences of abnormal return in the investment done by a company, particularly in the R&D and Product or Market categories. Dividing the types of investment into seven categories (Joint Venture, R&D, Diversification, Expansion, New Plant, New Project, and Capital Expenditure), [21] also found differences in abnormal return in those seven types of investments. This is because of the fact that the market's reaction towards investment decisions depends on the quality of a company's investment opportunity [21].…”
Section: Hypothesis Developmentmentioning
confidence: 87%
“…Thus supports the former research that investors tend to show their responses to news related to a company's system & technology innovation which brings back positive abnormal returns to the company [3]; [14]; [15]; [16]; [17]; [18]; [19] There are significant differences on investors' responses toward the system & technology innovation category and new product category. This is due to the fact that investors are able to differentiate between good investment and poor investment [19], also because each investment category represents different value in the eyes of investors [20]; [21]; [22].…”
Section: Introductionmentioning
confidence: 99%